"Peace with You": Exploring Translation Possibilities of the Peace Greeting in John 20 in Tagalog. Issue 1 (April 2023) - Arevalo, Rhoneil Mendoza
"Peace with you" in John 20 is widely understood as a Jewish greeting. But the context surrounding the Johannine peace salutation seems to suggest that it may have been meant to serve functions other than a greeting. These functional possibilities reflect the comprehensiveness of the meaning of peace in both the Old and New Testaments. A formal or word-for-word translation of "peace be with you" in a language like Tagalog ends up sounding artificial and unintelligible. Translation solutions are proposed for the different contexts in which the phrase occurs in John.